2018
DOI: 10.1111/iwj.12940
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and enablers to patient recruitment for randomised controlled trials on treatment of chronic wounds: A systematic review

Abstract: Randomised controlled trials represent the gold standard in intervention efficacy evaluation. However, suboptimal recruitment affects completion and the power of a therapeutic trial in detecting treatment differences. We conducted a systematic review to examine the barriers and enablers to patient recruitment for randomised controlled trials on chronic wound treatment. Review registration was under PROSPERO 2017:CRD42017062438. We conducted a systematic search of Ovid MEDLINE, EBSCOhost CINAHL, Ovid Cochrane L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
32
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(35 citation statements)
references
References 45 publications
(282 reference statements)
0
32
0
Order By: Relevance
“…The barriers to participant recruitment in RCTs in various health fields reported to date are classified into 4 major groups; these are: participant‐related, health professional‐related, practice‐related, and study‐related . These groupings were confirmed by a recent systematic review of barriers and facilitators to RCTs in chronic wound management conducted by Bugeja and associates . The main facilitators to patient recruitment for RCTs in other health fields were reported as follows: support provided by the project researchers to health professionals and health professionals’ perceived benefits of the study results for their practice .…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…The barriers to participant recruitment in RCTs in various health fields reported to date are classified into 4 major groups; these are: participant‐related, health professional‐related, practice‐related, and study‐related . These groupings were confirmed by a recent systematic review of barriers and facilitators to RCTs in chronic wound management conducted by Bugeja and associates . The main facilitators to patient recruitment for RCTs in other health fields were reported as follows: support provided by the project researchers to health professionals and health professionals’ perceived benefits of the study results for their practice .…”
Section: Introductionmentioning
confidence: 85%
“…A qualitative approach has helped us identify various recruitment enablers and some relevant suggestions on how to improve recruitment rate of RCTs on wound management, although enablers are rarely reported, as the results of the recent systematic review has indicated. 15 However, these identified enablers and proposed suggestions should be considered with caution because some of them may not always work. For example, the availability of researchers on-site was discussed by many participants as the main enabler, although it helped to slightly increase the recruitment rate at 1 site.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, they said that refreshers during the course of recruitment could have been helpful. Clinicians' insufficient trial‐related skills were frequently reported as a barrier to recruitment . Clinicians' training, particularly related to recruitment and retention of participants, was reported as one of the potential strategies to improve the recruitment rate .…”
Section: Discussionmentioning
confidence: 99%